(untitled) (Bulletin KNOB, 2002)
In the seventeenth century European expansion extended to foreign coasts all over the world. From icy seas to palm-shaded beaches discoveries were made, settlements arose and military actions were undertaken, when necessary - and obviously this always seemed to be the case. The Dutch followed the trend of the times, exploring the Asian, African and American continents, even as far as Antarctic and Australian regions. After the rise and fall of a handful of private companies, the East India Company for trade and commerce in the Far East (VOC, 1602) and the West India Company for the same purpose in the Americas (WIC, 1621) were founded. By that time important aims were the defense of the Republic’s international position during the Thirty Years’ War (1618-1648) and their own Eighty Years’ War with Spain (1568-1648). In their battle against Portugal as part of the Spanish crown and a strong Roman Catholic ally opposing the revolting Calvinist Low Countries, the Dutch invaded the Northeast of Brazil in 1630, after a badly prepared adventure, which did not even last a year, in Sao Salvador da Bahia in 1624. If this rich sugar country could be conquered, this would greatly damage the Iberian nations. And in fact, the successfully accomplished invasion by the Dutch admiral Lonck and commander Van Waerdenburgh in Pernambuco near the capital Olinda turned out to be the start of a large strategic and economic power. Establishing their position, the Dutch built a fair amount of fortresses and military constructions all along the coast of ’Dutch Brazil’. In 1999 the Archaeological Identification Mission, consisting of drs O.F. Hefting and the author, reported to the Dutch Ministry of Foreign Affairs and the Ministry of Education, Culture and Sciences, on the then discovered remains of twelve locations, among which those of Fort van der Dussen and Fort Ghijsseling. This article deals with the history of these two fortresses, erected by two merchants from the Province of Zeeland, in the fertile region of sugar plantations and orchards south of Recife. The Chamber of Zeeland with Middelburg was considered to be the most powerful in the board of the WIC, after the Chamber of the City of Amsterdam. Although nowadays there is not much left of these fortresses, a visit to the original places appeals to the historian’s imagination. By archaeological research a lot of the remains can still be found and conserved for later generations.